KARAKTERISTIK BENTUK DAN UKURAN SEL DARAH IKAN BETOK (Anabas testudineus) DAN IKAN GABUS (Chana sriata) - Hidayaturrahmah Hidayaturrahmah (Universitas Lambung Mangkurat, 2015)
The study was conducted to assess the characteristics regarding the size and shape of blood cells climbing perch and striped snakehead. Samples obtained from martapura river districts banjar, South Kalimantan. Blood examination carried using hematology method. Results showed that the cells form erythrocytes on climbing perch is round, while the oval-shaped striped snakehead. The Form of leukocytes, platelets, lymphocytes, monocytes, neutrophils, eosinophils and basophils Both betok fish and gabus fish everything Shaped round. characteristics of Blood cell climbing perch have red cell (eritrocyt) size of 7.36 ± 0.65 x 106 µm; Platelet count of 3.59 ± 0.32 µm, lymphocytes 5.11 ± 1.02 µm, monocytes 7.76 ± 1.36 µm, Eosinophils 8.74 ± 0.47 µm, Bashophil 8:24 ± 0.33 µm. characteristics size of blood cells striped snakehead are: erythrocytes 10.29 ± 0.33 µm, 3.59 ± 0.66 µm platelets, lymphocytes 6.85 ± 0.75 µm, monocytes 8.02 ± 0.41 µm, Eosinophils 7, 46 µm, Bashophil 9.63 ± 0.21 µm.